Qualidade de sementes e de mudas enxertadas de Passiflora nitida Kunth. sob maracujazeiro-azedo - Araújo, Victória Pontes Damasceno (2023)
The objective of this work was to evaluate the biometry of P. nitida fruits, the percentage of seed germination and the vegetative performance as a function of the grafting method of P. nitida on four commercial cultivars of P. edulis ('BRS Rubi do Cerrado', 'BRS Sol do Cerrado', 'BRS Gigante Amarelo' and 'FB 200'), leaving a pair of leaves partially cut (leaf budding) or the grafting region covered with a sachet (wet chamber). The studies were divided into two chapters. The first deals with the evaluation of the biometric characteristics of the fruits such as: diameter, length, total mass, peel mass, pulp mass and number of seeds per fruit, where differences in size, mass and quantity of seeds per fruit were obtained. The seeds were submitted to soaking to overcome dormancy for 6 and 12 hours at temperatures of 25 and 30 °C in water or in gibberellic acid solution at 4,000 mg L-1 (GA3). The germination of P. nitida seeds was higher in treatments with pre-soaking in GA3 solution. The second chapter studied the process of grafting four commercial cultivars ('BRS Rubi do Cerrado', 'BRS Sol do Cerrado', 'BRS Gigante Amarelo' and 'FB 200') onto wild passion fruit. Thus, when the seedlings reached 98 and 58 days for P. nitida and commercial cultivars, respectively, it was defined as the moment of grafting and 10 seedlings of the rootstock and each of the four commercial cultivars were evaluated for fresh and dry mass of the aerial part and roots, length of the aerial part and root and neck diameter. Then the full-grafting procedure was performed, testing sachet (wet chamber) or a pair of leaves (toelet). The cultivar that had the best performance when grafted on P. nitida was 'BRS Sol do Cerrado'.